2017
DOI: 10.1111/iju.13325
|View full text |Cite
|
Sign up to set email alerts
|

Current status of clinical trials assessing oncolytic virus therapy for urological cancers

Abstract: Oncolytic virus therapy has recently been recognized as a promising new option for cancer treatment. Oncolytic viruses replicate selectively in cancer cells,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 97 publications
0
33
0
1
Order By: Relevance
“…At preclinical level, it has been shown that oncolytic adenoviruses are successful in treating MIBC [37]. Several other oncolytic viruses have shown efficacy in urothelial carcinomas and some are currently tested in clinical trials [38]. Combination of oncolytic viruses with immune checkpoint inhibitors and targeted therapies has been proven to be a successful strategy to enhance the efficiency of therapy response to oncolytic virus [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…At preclinical level, it has been shown that oncolytic adenoviruses are successful in treating MIBC [37]. Several other oncolytic viruses have shown efficacy in urothelial carcinomas and some are currently tested in clinical trials [38]. Combination of oncolytic viruses with immune checkpoint inhibitors and targeted therapies has been proven to be a successful strategy to enhance the efficiency of therapy response to oncolytic virus [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, oncolytic adenoviruses have been commonly used in clinical trials for cancer gene therapy. 14,15 Among them, the cancer-targeting gene virotherapy (CTGVT) strategy 16 might be a useful strategy for the treatment of advanced or metastatic cancer. For example, inserting the vascular endothelial cell growth inhibitor (VEGI) into a selectively replicating adenovirus with an E1B-55kDa gene deletion (ZD55) to construct ZD55-VEGI-251 leads to a much more severe cytopathic effect than control viruses on human cancer cell line HeLa, hepatoma cell line SMMC-7721, and CRC cell line SW620.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the OV Talimogene Laherparepvec (Imlygic Âź , T‐VEC) has recently been licensed in the United States and Europe for the treatment of melanoma . In the few early‐phase clinical trials that have included PCa patients, safety and efficacy data were also encouraging . However, most of the OVs currently under development need to be applied intratumorally, as pre‐existing or rapidly induced neutralizing antiviral antibodies limit the systemic delivery to the tumor tissue and thereby the efficacy in metastatic disease.…”
mentioning
confidence: 99%
“…7,8 In the few earlyphase clinical trials that have included PCa patients, safety and efficacy data were also encouraging. 9 However, most of the OVs currently under development need to be applied intratumorally, as pre-existing or rapidly induced neutralizing antiviral antibodies limit the systemic delivery to the tumor tissue and thereby the efficacy in metastatic disease. Among the OVs currently in the development pipeline, vesicular stomatitis virus (VSV) carrying the envelope protein (GP) of the lymphocytic choriomeningitis virus, VSV-GP, has several outstanding features: (i) There is practically no pre-existing immunity against VSV-GP in the general population and VSV-GP does not readily induce neutralizing antibodies.…”
mentioning
confidence: 99%